Personality styles and stress coping styles in university students of Beca 18 Program - González Sarmiento, Olga (2020)
styles to stress in students belonging to the Beca 18 Program at a private university in Lima? Theodore Millon’s (1994) personality theories and Frydenberg and Lewis’ (1993) stress coping theories were used as theoretical support for the research. The study presents a quantitative approach, ex post facto correlational design, applied to a sample of 83 students. The results showed that personality styles play a mediating role in stress coping styles in individuals with low motivational goals and poor interpersonal relationships. The personality styles that predominate in the students of the sample correspond mostly to the scales of interpersonal relationships, motivational goals and cognitive modes. The styles of openness, modification, affectivity, innovativeness and submissiveness correlated with the problem-solving styles. Innovativeness and extraversion styles correlated with non-productive coping style. Finally, personality styles did not correlate with the coping style referred to as referral to others.